Does Worrying Matter? Priming and Attitudes Toward Mask Wearing in a Midwestern State. (November 2021) - Huang, Francis L.; Reinke, Wendy; Herman, Keith
Due to the spread of the coronavirus disease 2019 (COVID-19), the use of protective measures (e.g., mask wearing and social distancing) has become an important public health concern. Despite being an effective and low-cost measure, mask wearing in the U.S. is a contentious issue. We investigated data coming from a natural experiment ( n  = 1, 993) collected in a Midwestern state where survey questions about mask wearing and COVID-19 were presented in a random order. Primed respondents ( n  = 1, 011), who answered COVID-19 related questions prior to the mask questions, indicated no differences in the efficacy of masks in stopping the spread of the virus compared to nonprimed respondents ( n  = 982). However, primed respondents who were not worried about getting sick were 37% less likely to believe in the efficacy of masks compared the nonprimed, nonworried respondents. Nonworried respondents represent a high-risk group who are likely not to wear a mask. Implications for the messages used in public health campaigns to elicit a change in behaviors are discussed.